Pathologic tearfulness after limbic encephalitis: a novel disorder and its neural basis - Argyropoulos, GPD; Loane, C; Roca-Fernandez, A; Moore, L; Lage-Martinez, C; Loane, C; Roca-Fernandez, A; Gurau, O; Lage-Martinez, C; Moore, L; Irani, SR; Gurau, O; et al. (American Academy of Neurology, 2020)
Objective We investigated the nature and neural foundations of pathologic tearfulness in a uniquely large cohort of patients who had presented with autoimmune limbic encephalitis (aLE).